SENJATA API ALAM MELAYU - Wan Mohd Dasuki Wan Hasbullah (Dewan Bahasa dan Pustaka, 2020)
On Malay traditional knowledge systems related to the use of firearms and weapons since the 16th century transcribed in Malay manuscript.